The Iraqi Female Writers: The Beginning and a Steady Proliferation - Mahmoud, Amel (Humanities Journal of University of Zakho, 2022)
This present research aims at answering that need tracing back the first female literary attempts in Iraq at the dawn of the twentieth century. Moreover, the research seeks to define the characteristics of such writings and examine the conditions that lead to their growth and flourishment. While scrutinizing the main female literary figures and their reputed literary works, the discussion sheds light on particular historical and social factors that genuinely contributed in the nourishment of the literary production of those authors such factors as; education, the aristocratic class and later the birth of the middle class and the influence of the contact with the western civilization. All these vital factors assisted, to a great extent, in the increase and diversity of the literary production of the Iraqi female writers from the dawn of the twentieth century. The research endeavors to cover the first half of the twentieth century, which is regarded by many researchers as the period that witnessed the birth of the female literary writings. The research deals with women literature of the following two decades; the sixties and the seventies. It is necessary to clarify that the research does not include the period of the eighties as the country went through the Iran-Iraq War (1980-1988). During this period a new kind of literature emerged named Adab al-Ma’raka, War Literature. This kind of literature is rich with literary outputs by the Iraqi female authors with diverse artistic qualities, themes and narrative techniques. This type of literature requires an independent study with a through discussion which the present research, with its limited space and scope, cannot sufficiently tackle.